THE PHILOSOPHY OF IQRA` ON ISLAMIC EDUCATION - Ahmad Wahyu Hidayat (State Institute of Islamic Studies (IAIN) Palu, 2018)
Islam is a religion that gives great attention to science. Attention is evidenced by the revelation of the first al-Alaq 1-5 are five initial sentences that can build Islamic civilization in the world. In a dynamic society, learn to play a role that determines the existence and development of the society, because education is the effort to preserve, and transfer as well as transforming the values of its kind in all its aspects and to future generations. Based on this background, the researchers will explain the meaning of iqra`, Any verses about iqra`, and how philosophy iqra`. Based on the analysis, researchers concluded that iqra` said in al-‘Alaq verses 1-5: (1) repeated twice in this verse. iqra` first can be interpreted or translated more broadly to understand, analyze, examine, delivering, studying, researching, knowing, and so on which is based the name of God the almighty creator, while iqra` which both describes the benefits, give understanding, can seep into the soul as an attempt to explore and examine the science that has been obtained; (2) ‘allama, human teaching with stationery so teach men to things that are not yet known; and (3) qalam, a tool that can produce a work that can be indoctrinated by a man who could only be done using qalam.